2007
DOI: 10.1002/cncr.22891
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid for the treatment of myeloid malignancies

Abstract: Valproic acid (VPA) has been used as an anticonvulsant for decades. Recently, it was demonstrated that VPA also acts as a histone deacetylase inhibitor and induces differentiation and apoptosis in a variety of malignant cells in vitro. The effect of VPA on tumor cells differs according to cell type, degree of differentiation, and underlying genetic alterations. Clinical trials with VPA have focused on acute myeloid leukemia and the myelodysplastic syndromes. When it was used as monotherapy or in combination wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
77
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(83 citation statements)
references
References 71 publications
4
77
0
1
Order By: Relevance
“…Since the clinical use of HDAC inhibitors is increasing, it is important to define the effects of this family of compounds on the normal hematopoietic compartment. While results of phase I clinical trials with HDAC inhibitors suggest no unfavorable effects on the normal progenitor compartment, 24,35,37,38 our data clearly show that both the choice and concentration of HDAC inhibitor can greatly affect the proliferative and differentiation capacity of CD34 + hematopoietic progenitor cells. Furthermore, our results suggest that these effects may be mediated by non-histone targets.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Since the clinical use of HDAC inhibitors is increasing, it is important to define the effects of this family of compounds on the normal hematopoietic compartment. While results of phase I clinical trials with HDAC inhibitors suggest no unfavorable effects on the normal progenitor compartment, 24,35,37,38 our data clearly show that both the choice and concentration of HDAC inhibitor can greatly affect the proliferative and differentiation capacity of CD34 + hematopoietic progenitor cells. Furthermore, our results suggest that these effects may be mediated by non-histone targets.…”
Section: Discussionmentioning
confidence: 65%
“…23 Valproic acid (VPA), a short chain fatty acid and potent class I/IIa HDAC inhibitor, has been extensively studied in preclinical and clinical trials involving hematologic malignancies. 24,25 Studies in patients with advanced myeloid leukemia and myelodysplastic syndromes have shown that treatment with VPA, as monotherapy or in combination with retinoic acid, results in a reduction of malignant blast cells and hematologic improvement. [26][27][28] In addition, in an ex vivo model of acute leukemia, it has been demonstrated that VPA has the potential to relieve transcriptional repression resulting in cellular differentiation of leukemic blast cells.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, VPA has been shown to induce the death of chronic lymphocytic leukemia cells, 47 and several trials are currently exploring its activity against various types of cancer, including hematologic malignancies. 48 Depsipeptide, another HDAC inhibitor, has demonstrated efficacy against primary ATL cells. 49 Moreover, in a murine model of human ATL, 50 HDAC inhibitors are able to trigger growth arrest and death of HTLV-1-infected cell lines and ATL cells via activation of the death-receptor pathway and potentialization of tumor necrosis factor-related apoptosis-inducing ligand response.…”
Section: Discussionmentioning
confidence: 99%
“…12 The anti-tumor properties of VPA have been observed in many cancer types, such as prostate cancer, 13 breast cancer, 14 glioma, 15 neuroblastoma 16 and in hematological malignancies. [17][18][19] Recently, our group showed that VPA at low pharmacological concentration could induce apoptosis of CLL B cells in vitro. 20 Bokelmann and Mahlknecht 21 showed decrease in the BCL-2/Bax ratio in CLL B cells treated with VPA in vitro and Bouzar et al 22 reported that valproate synergizes with purine nucleoside analogues to induce apoptosis of CLL B cells.…”
Section: Introductionmentioning
confidence: 99%